Description Of Quality Of Life For Post Partum Mothers During The Covid-19 Pandemic - Anisa Nismawati; Rilyani Rilyani; Aryanti Wardiyah (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Latar Belakang: Hasil dari prasurvey didapat jumlah ibu post partum di Puskesmas Sukaraja sebanyak 1.111 ibu post partum , sedangkan di Puskesmas Kedaton diketahui sebanyak 1.296 ibu post partumTujuan: Diketahui gambaran kualitas hidup ibu post partum pada masa pandemic covid-19.Metode: Jenis penelitian kuantitatif, Jumlah ibu post partum usia 0-42 hari di Puskesmas Sukaraja sebanyak 1.111 ibu post partum dan di puskesmas Kedaton sebanyak 1.296 ibu post partum, pemilihan sampel menggunakan rumus isaac sehingga didapat S = 100 sampel. Tehnik sampling pada penelitian ini adalah purposive sampling. Anlisa data univariat dengan distribusi frekuensi.Hasil : Gambaran kualitas hidup ibu post partum di Puskesmas Sukaraja dengan kategori baik 1 responden (2,0%), sangat baik sebesar 49 responden (98,0%). Sedangkan di Puskesmas Kedaton dengan kategori baik 7 responden (14,0%), dan sangat baik sebesar 43 responden (86,0%).Kesimpulan Gambaran kualitas hidup ibu postpartum 98% sangat baik di Puskesmas SukarajaSaran : Kepada peneliti selanjutnya untuk meneliti factor yang mempengaruhi penegeluaran ASI pada ibu post partum seperti nutria selama hamil dan factor yang mempengaruhi pengeluaran kecemasan pada ibu post partum seperti keadaan pandemi Covid-19. Kata Kunci :Covid 19, Ibu NIfas,Kualitas Hidup ABSTRACT Background: The results of the pre-survey found that the number of post partum mothers at the Sukaraja Health Center was 1,111 post partum mothers, while at the Kedaton Health Center it was known that there were 1,296 post partum mothersObjective: To know the description of the quality of life of post partum mothers during the Covid-19 pandemic.Methods: This type of research is quantitative, the number of post partum mothers aged 0-42 days at the Sukaraja Health Center was 1,111 post partum mothers and at the Kedaton Health Center there were 1,296 post partum mothers, the sample selection used the isaac formula so that S = 100 samples were obtained. The sampling technique in this study was purposive sampling. Univariate data analysis with frequency distribution.Results: A description of the quality of life of post partum mothers at the Sukaraja Health Center with good category 1 respondent (2.0%), very good 49 respondents (98.0%). Meanwhile, in the Kedaton Health Center, 7 respondents (14.0%) were in good category, and 43 respondents (86.0%) were very good.Conclusion The quality of life for postpartum mothers is 98% very good at the Sukaraja Health CenterSuggestion: For future researchers to examine the factors that influence breastfeeding in post partum mothers such as nutria during pregnancy and factors that influence anxiety expenditure in post partum mothers such as the Covid-19 pandemic. Keywords: Covid 19, Postpartum Mothers, Quality of Life